Introduction to international disaster management - Coppola, Damon P. (Butterworth-Heinemann, 2021)
Introduction to International Disaster Management, Fourth Edition, offers an unbiased, global perspective for students and practitioners alike. It provides a comprehensive understanding of the disaster management profession, covering the varied sources of risk and vulnerability, the systems that exist to manage hazard risk, and the many different stakeholders involved, from individuals to global organizations. This text also serves as a reference on scores of disaster management topics, including various technological and intentional hazards, on international disaster management structures and systems, on global humanitarian spending and support, and much more. Taking a real-world approach with considerable illustration through case studies and recent and historical disaster events, this book prepares students interested in joining the disaster management community to understand the work they will be doing. In addition, it assists those who already work with the disaster management community by helping them better navigate this complex environment.